Borderless Violence Involving Transnational Migrants: The Case Study of the Uighur from Xinjiang - Setthamalinee, Suchart (ASIA PARIDARSANA, 2017)
Over the past few years, Thailand has been experiencing a number of violent incidents involving transnational migrants, including the Uighur from Xinjiang, China. The violence has taken place both in Thailand and elsewhere. The violent incident in Thailand was the explosion in the Ratchaprasong area, which lies in the heart of Bangkok. The case on this incident is still in the process of legal action against the accused, who are all Uyghur. The violence outside Thailand was the destruction of the Consulate-General office of Thailand in Istanbul, Turkey. This incident still remains puzzling to the Thai people in general: who are the Uyghur? Where did they come from? Why did they commit violence in Thailand? This research article aims to answer those questions, and also to find appropriate ways to deal with transnational migrants. The study found that the Uighur people have a history of their own for thousands of years. Later, they were adversely affected by various policies of the Chinese government, such as those restricting the freedom of religious practice, imposing discrimination, violating human rights, and also exploiting the economic and resource interests in the area. The Uighur have thus been so unhappy, and some of them have tried to resist the Chinese central government and moved to other countries. Thailand has become a target country being used by the Uighur migrants as a passage to some other countries. Therefore, the Thai government needs to take appropriate measures to maintain a balance in the treatment of this group to avoid complications which may affect the country’s long-term national interests.